Behavioral responses of zebrafish depend on the type of threatening chemical cues - Abreu, Murilo S.; Giacomini, Ana Cristina V.; Gusso, Darlan; Koakoski, Gessi; Oliveira, Thiago A.; Marqueze, Alessandra; Barreto, Rodrigo Egydio [UNESP]; Barcellos, Leonardo J. G. (Springer Nature, 2016)
In fish, defensive reactions are induced by different chemical cues that emanate from sense-related stresses [physical, chemical, and visual (visual contact with predator)] or food stresses (acute fasting and chronic food restriction). Using a shuttle box with a two-chamber unmixed laminar flow that allowed fish to remain or flee from a chemical cue, we showed that the avoidance response depended on the type of the chemical cue. We show that zebrafish (Danio rerio) retreated from water conditioned with chemical cues released by chemically or physically stressed fish and acutely fasted fish, but not from water with cues from fish experiencing visual contact with predatory fish or fish suffering from chronic food restriction. Our data reinforced the hypothesis that fish use a combination of information and the context of the situation to determine their evasion strategy.
Keywords: Attraction; Aversion; Chemical cues; Defensive behavior; Zebrafish